(untitled) (Journal of Surgical Sciences, 2019)
Background: Operations on breast are routinely performed under general anesthesia. Avariety of local and regional techniques have been described for breast surgery with thegoal of reducing the complications associated with general anaesthesia. Objective: To assess the feasibility of thoracic epidural anaesthesia as sole anesthetictechnique for breast surgery. Methods: This study was conducted on 32 cooperative female patients of age group42-55 year. T5-T6 or T4-T5 space was used for insertion of epidural catheter. lnjLidocaine 2% 12 ml was injected through the catheter as anaesthetic agent. lnj Tramadol50- 100 mg used epidurally for postoperative relief till 48 hours postoperatively.Demographic characteristics of the study population, any coexisting disease, type ofsurgery performed, duration of surgery, degree of intraoperative analgesia, incidence ofcomplications related to TEA, and its efficacy in postoperative pain relief were observedand analysed. Results: Out of 32 patients most of them (11) were in between 51-55 years. 10 out of32 had coexisting disease. 5 patient had hypertension and one had asthma. Modifiedradical mastectomy (MRM) was most frequently performed operation (24). 21 patientcomplained no pain during the operation and 5 patient complained mild discomforttowards end of operation. 4 patient developed bradycardia during the operation whichwas managed by inj. Atropin. Post operative analgesia was satisfactory. Conclusion: Midthoracic epidural anaesthesia technique is a safe alternative acceptablemethod for various breast surgery with excellent postoperative pain relief and earlyrecovery. Journal of Surgical Sciences (2017) Vol. 21 (1) :29-32